The legal model for the crime of normalization with the Zionist entity - PHD TEACHER :ZAID AJMI BSHEET (The college of law and political science journal, 2024)
The attention of our research, tagged with (the legal model of the crime of normalization with the Zionist entity), was directed to many aspects closely related to the political and social reality. Criminal activity and the general concepts of the crime of normalization were achieved, and we also touched on the criminalization contained in the Penal Code No. 111 of 1969 for the crime of normalization in Article 201, and what aroused our interest in the matter is that the law defines gradual penalties, but rather singles out the act and makes its punishment death, and one of the basic matters that our study focused on It is the development of a legal model for the crime of normalization, starting with the development of general concepts of the crime and its legal basis, and then clarifying its elements, the penalties resulting from it, and its scope of application. He did not specify the type of punishment imposed, and the text was absolute on all punitive texts, and we recommended the legislator to abolish life imprisonment and keep the death penalty exclusively for the categories mentioned in Article (9) of the law in question. It is not possible for the legal status of the President of the Republic to be equal when he rises By belonging to any institution of the Zionist entity with a citizen who does not have any job, both of them are subject to the death penalty or life imprisonment.